Financial Technologies in the Banking Sector: Prospects and Security - Mukusheva, A.G.; Zholamanova, M.T.; Kuchukova, N.K. (BUKETOV BUSINESS REVIEW, 2021)
Object: Annually financial technologies have an increasing impact on the banking sector. The article provides definitions of the term "financial technologies" by international organizations, foreign, Russian and Kazakh experts. In the context of the fourth industrial revolution, the relevance of the topic is justified by a sharp increase in the development of financial technologies and spread of digitalization in the banking sector. The purpose of the research is to survey the impact of digital technologies on the financial sector. Methods: The main categories of financial technologies in the world and in Kazakhstan, in particular, are considered. The strengths and weaknesses, opportunities and threats of financial technologies in the banking sector are analyzed. Findings: Digital transformation paves the way for a wide range of mobile data deployments that require ongoing security. In addition, the active development of information technology should stimulate the financial sector to be flexible and apply innovative approaches in all areas. The material also provides the prerequisites and reasons for digitalization in the area of banking services. Conclusions: The transition of traditional types of banking services to a new level of technological development shows a direct relationship between the development of financial technologies and data security. In this regard, it seems relevant to effectively allocate priorities, taking into account the characteristics and specifics of each subject of banking activities. In an increasingly competitive environment, the most rational and digitally oriented strategy of the bank is becoming important.